2017
DOI: 10.1016/j.bjorl.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Aging and wave-component latency delays in oVEMP and cVEMP: a systematic review with meta-analysis

Abstract: The latency of oVEMP n1 wave component and latencies of cVEMP p13 and n23 wave components are longer in the elderly aged >60 years than in young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…Therefore, it is indispensable to establish the normal range of BCV-induced VEMP for different age groups. Several previous studies have reported the influence of age on oVEMP and cVEMP parameters ( 17 , 24 , 25 , 27 31 ). Most studies showed a significant decline in the response rates, prolongation of latencies, and reduction of oVEMP and cVEMP amplitudes with increasing age ( 24 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is indispensable to establish the normal range of BCV-induced VEMP for different age groups. Several previous studies have reported the influence of age on oVEMP and cVEMP parameters ( 17 , 24 , 25 , 27 31 ). Most studies showed a significant decline in the response rates, prolongation of latencies, and reduction of oVEMP and cVEMP amplitudes with increasing age ( 24 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Age-related morphological changes may occur in the vestibular system from the end organs to the central nuclei, including loss of hair cells, decreased numbers of vestibular nerve cells, and loss of neurons in the vestibular nucleus ( 20 23 ). Therefore, the effects of advancing age on the response rate, latency, and amplitude of ACS-VEMPs have been well explored ( 24 , 25 ). However, the age-related impact on the B81-VEMPs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The findings in this study are consistent with previous studies that showed prolonged latency, which may be associated with demyelination of axons (this reduces conduction velocity). 19,20 Macambira et al 21 reported that the latency component of oVEMP was delayed in older adults and it may be associated with a reduction in the number of neurons. Severe demyelination of axons due to OSAS may contribute to absent oVEMP responses because of conduction block.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Macambira et al. 21 reported that the latency component of oVEMP was delayed in older adults and it may be associated with a reduction in the number of neurons. Severe demyelination of axons due to OSAS may contribute to absent oVEMP responses because of conduction block.…”
Section: Discussionmentioning
confidence: 99%
“…Dentre as limitações do presente estudo está o escasso número de estudos que investigaram os limiares de resposta do VEMP, principalmente em indivíduos sem alterações otoneurológicas, dificultando assim a confirmação ou questionamento crítico mais aprofundado dos dados encontrados neste estudo 10,15,16,17,18,19,20,21 . Não foi possível realizar a comparação entre os sexos sobre os parâmetros do exame, devido à dificuldade em recrutar indivíduos do sexo masculino para o estudo.…”
Section: Conclusãounclassified